EXPLORING STUDENTS' PERCEPTIONS OF THE CONTROL OVER LEARNING CONTENT IN AUTONOMOUS ENGLISH LEARNING - Rabiatul Adawiyah (Prologue: Journal on Language and Literature, 2024)
The limited classroom learning time makes autonomous learning skills crucial for students to enhance their English language proficiency. However, the lecturer should also control students’ autonomous learning including the learning content. This study explores students' perceptions of the control over learning content by students and the lecturer for promoting autonomous English learning. The researchers employed a qualitative method with interviews, observation, and documentation to gather the data. There were 15 non-English department students as the subject of the study. The finding revealed that the students had autonomy in controlling their English learning content such as determining the content reference, the content form, and adapting to needs. Although they began to have autonomy, they needed the lecturer’s role to support them. It was remainder for the lecturer that the role of facilitator, counsellor, and evaluator in English language teaching. Therefore, exploring students’ perceptions related to their autonomy in English learning is important to enhance teaching further.